Macroeconomic Management and the Devolution of Fiscal Powers. (IMF Working Papers; Working Paper, 2002)
Several of the transition economies are devolving fiscal authority to subnational governments at a time when it is also important to consolidate fiscal policy. This can be problematic because, without appropriate care, the central government's ability to determine the level and structure of revenues, public spending, and borrowing may well diminish as fiscal policy is devolved. This paper focuses on how the center can maintain its ability to conduct fiscal policy while devolving revenue, spending, and borrowing powers to lower levels of government. Empirical evidence shows that countries with good governance have maintained fiscal control despite a high degree of fiscal devolution. And decentralization is associated with better fiscal outcomes for middle-income countries with strong governance. Fiscal management issues are explored in four key areas: budget coordination mechanisms at the macro level tax-effort incentives and revenue-sharing mechanisms expenditure control and hard-budget constraints and criteria and rules for borrowing.